Effectiveness of contextualized digital worksheets (e-lkpd) using liveworksheets to enhance mathematical critical thinking and self-regulated learning - Helmy Wahyu Widiarti; Anton Jaelani (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The integration of digital technology in mathematics education is essential for fostering 21st-century skills, particularly mathematical critical thinking and self-regulated learning. However, conventional teaching practices still dominate classrooms, limiting students’ active engagement and independent learning. The use of contextualized Electronic Student Worksheets (E-LKPD) integrated with Liveworksheets and real-life contexts such as online shopping offers a promising approach to create meaningful and student-centered learning experiences. Aims: This study aims to develop a valid and practical contextualized E-LKPD using Liveworksheets and to examine its effectiveness in enhancing students’ mathematical critical thinking skills and self-regulated learning. Method: This study employed a Research and Development (R&D) approach using the ADDIE model. Participants were eighth-grade students at SMP Negeri 2 Cikarang Pusat, divided into experimental and control groups. Data were collected through validation sheets, questionnaires, tests, observations, and interviews. Data analysis used a mixed-method approach, including descriptive qualitative analysis and quantitative analysis through normality, homogeneity, and independent samples t-tests. Results: The results indicate that the developed E-LKPD is valid and practical. Statistical analysis showed no significant difference in students’ mathematical critical thinking skills between the experimental and control groups (p = 0.412), although the experimental group demonstrated slightly higher mean scores. In contrast, a significant improvement was found in self-regulated learning (p < 0.001), with higher mean scores in the experimental group. Conclusion: The contextualized E-LKPD effectively enhances students’ self-regulated learning but shows limited impact on mathematical critical thinking. Further optimization in instructional design, implementation duration, and pedagogical integration is required to improve higher-order thinking outcomes.